Social protection committee annual report 2018. Review of the social protection performance monitor (SPPM) and developments in social protection policies: Annex 2. SPPM Country Profiles (Luxembourg, 2018)
"The report highlights that the social situation in the EU continues to benefit from the economic recovery and the reform efforts made by Member States in recent years. Of particular note is the continued improvement in the labour market situation, with significant reductions in unemployment, while deprivation and social exclusion are also declining. Nevertheless, the recovery has so far had a rather mixed and sometimes limited impact on the other social indicators, and Europe remains far from reaching the Europe 2020 poverty and social exclusion target. Several trends of concern are still apparent, including the still widening depth of poverty risk in many Member States, the rising trend in in-work poverty risk in several countries, and the still increasing risk of poverty for people in (quasi-)jobless households."